The story of Japan's Ohmi merchants : The precept of Sanpo-yoshi - Suenaga, Kunitoshi (Japan Publishing Industry Foundation for Culture, 2019)
This book reveals the history of the Ohmi region and its merchants, who shaped Japanese-style management. It introduces key concepts like sanpo-yoshi (three-way satisfaction), corporate social responsibility, and innovation. These principles have driven the long-lasting success of Japanese businesses. The book highlights the ongoing relevance of Ohmi merchants' philosophy for both scholars and general readers.